An evaluation of binomial model with implied volatility in pricing warrant / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Mohd Abduh, Wan Mohd Yaseer; Mohd Idris, Mohd Fazril Izhar; Saian, Rizauddin (Universiti Teknologi MARA, Perlis, 2018)
There are various models that can be applied in pricing warrant. In this study, the Binomial model with implied volatility was chosen to calculate the warrant price. The price of warrant obtained from the model will be compared with the actual price to check the accuracy and consistency of the warrant price. Several companies which issues warrant will be randomly selected from Bursa Malaysia list. Information on underlying shares and warrants were collected from UiTM data stream start on January 2016 until May 2017. Parameters like exercise price or strike price, interest rate, maturity date and volatility are involves in pricing warrant. This study also discussed on moneyness which determines either the mother shares of the warrant are in-the-money, at-the-money or out-the-money.